Strength and conditioning for adolescent endurance runners - Blagrove, R. C.; Howe, L. P.; Howatson, G.; Hayes, P. R. (Strength and Conditioning Journal, 2020)
For the adolescent athlete who chooses to specialize in endurance running, strength and conditioning (S&C) activities provide a means of enhancing several important determinants of performance and may reduce the risk of overuse injury. It is recommended that adolescent endurance runners include at least 2 S&C sessions per week that comprise movement skills training, plyometric and sprint training, resistance training, plus exercises designed to target specific tissues that are vulnerable to injury. This article describes how these modalities of training can be integrated into the routine of adolescent endurance runners.